Analytical Description of the Temperature Field Induced by Laser Heat Source with Any Trajectory. (2016) - Winczek, Jerzy; Modrzycka, Agata; Gawrońska, Elżbieta
Abstract: The paper describes a three-dimensional temporary temperature field in the semi-infinite body caused by a moving laser heat source with any trajectory. In considerations the model of the surface heat source with the Gaussian distribution of power density was adopted. The trajectory of the source was approximated by straight sections. The calculation model of the temperature field takes into account changes in temperature caused by successive passes of the laser (temperature rise associated with the source action the source and cooling areas previously heated). Temperature field calculations in a rectangular steel member were carried out. The results of the calculations were illustrated by distributions of temporary and maximum temperature in a heated element.